Storage cost induced by a large substitution of nuclear by intermittent renewable energies: The French case. (December 2019) - Percebois, Jacques; Pommeret, Stanislas
Abstract: This paper explains some adverse effects due to a massive injection of renewables when electricity storage is not available, such as a fall of electricity prices on the spot market or a crowding-out effect for nuclear power stations due to the merit order logic. From the French experience, it presents a model that calculates the additional cost of electricity production when the share of nuclear generation is reduced to 50% instead of 72% today and when, in compensation, renewable energy (wind and solar) is stored either by batteries or by power-to-gas. The simulations minimize the cost of the energy mix by optimizing the electricity storage mix: batteries (daily storage) and Power-to-Gas/Gas-to-Power (seasonal storage). The paper also estimates the negative externalities of intermittent renewable energies that lie in between 44 and 107 €/MWh. It also examines the impact on the merit order when those negative externalities are accounted for. Finally, the simulation results lead us to provide some recommendations concerning R&D electricity storage policy and electricity mix fine tuning. Highlights: Necessity to introduce the negative externalities in the merit order framework. Necessity to adjust the CO2 ton price to finance the energy storage. Estimation of the negative externalities of intermittent renewable energies.